1989
DOI: 10.1111/j.1095-8649.1989.tb02960.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of brown trout, Salmo trutta L., in a tributary in Brittany (France): spawning and juveniles

Abstract: The colonization by both resident and migrating spawner populations of brown trout and the characteristics of resident and migrating juveniles derived from the two populations have been studied in a brook and its tributary over 4 years. Resident trout spawns mainly in the upstream part of the brook and migrating trout in the downstream part. There are density and growth variations for the two age classes (0+ and 1 +) ofjuveniles in autumn according to the year and the environment. In the brook, the population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
11

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 21 publications
4
27
0
11
Order By: Relevance
“…Although in some cases there seems to be a certain spatial segregation between these two morphae (Bagliniere et al, 1989), the lack of reproductive isolation, clearly demonstrated by several authors (Campbell, 1977;Jonsson, 1985), is a sound reason for consider- Svärdsom & Fageström (1982) and Jonsson (1982) could check the existence of inherited variation in the trout's tendency to migrate by studying different stocks or populations in this species. On the other hand, the biochemical analysis carried out by Ryman (1983), with several populations of Brown and Sea Trout, revealed the existence of slight genetic differences between these ecological forms.…”
Section: Discussionmentioning
confidence: 99%
“…Although in some cases there seems to be a certain spatial segregation between these two morphae (Bagliniere et al, 1989), the lack of reproductive isolation, clearly demonstrated by several authors (Campbell, 1977;Jonsson, 1985), is a sound reason for consider- Svärdsom & Fageström (1982) and Jonsson (1982) could check the existence of inherited variation in the trout's tendency to migrate by studying different stocks or populations in this species. On the other hand, the biochemical analysis carried out by Ryman (1983), with several populations of Brown and Sea Trout, revealed the existence of slight genetic differences between these ecological forms.…”
Section: Discussionmentioning
confidence: 99%
“…Ceci peut s'expliquer par un phénomène de migration à une plus large échelle des individus précoces au moment de la reproduction (maturation sexuelle possible dès 1+ dans le Massif Armoricain, voir BAGLINIÈRE et al 1987). En avril, on assiste à une sensible augmentation numérique de individus d'un an et plus sur le secteur, ce réajustement des densités se faisant probablement à la faveur des mouvements de juvéniles d'un été depuis la zone amont et les sous-affluents (BAGLINIÈRE et al, 1989).…”
Section: Discussionunclassified
“…Dès l'hiver et surtout au début du printemps, on assiste à la dispersion des juvéniles d'un été (Figure 6, D) depuis les zones d'amont et sous-affluents fortement peuplés vers l'aval du ruisseau ou le cours principal (BAGLINIÈRE et al, 1989). Les juvéniles 1+ entament leur deuxième saison de croissance, et les faciès profonds du ruisseau ont surtout valeur d'habitat de repos et refuge.…”
Section: Bilan De L'utilisation De L'habitat Par Le Juvénile En Ruisseauunclassified
“…a) Le taux de mortalité naturelle entre l'âge 0+ et 1+ qui est déjà de l'ordre de 40 à 70 % pour les individus sauvages (BAGLINIÈRE et al, 1989 ;ELLIOTT, 1989), pourrait être supérieur pour les individus domestiques du fait d'une moins bonne adaptation de ces poissons au milieu torrentiel, notamment en période hivernale. b) Une autre hypothèse pouvant expliquer la disparition des truites marquées du site d'alevinage est que les truites domestiques auraient une plus grande aptitude à la dévalaison que les individus sauvages (SKROCHOWSKA, 1969 ;CUINAT, 1971 ;GUYOMARD, 1991).…”
Section: Discussionunclassified